2001
DOI: 10.1042/bj3550529
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and translational mechanisms of cytochrome b5 reductase isoenzyme generation in humans

Abstract: Cytochrome b5 reductase (b5R) is an essential enzyme that exists in soluble and membrane-bound isoforms, each with specific functions. In the rat, the two forms are generated from alternative transcripts differing in the first exons. In contrast, the biogenesis of b5R isoforms in the human is not yet well understood. In the present study we have detected three novel alternative exons, designated 1S, S′ and 1B, located between the first alternative exon 1M and the common second exon in the human b5R gene. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…NADH cytochrome b 5 reductase is an FAD-containing protein with soluble and membrane-bound forms, each the product of the same gene through alternative promoters and alternative splicing (Tomatsu et al, 1989;Leroux et al, 2001). Both soluble (approximately 32 kDa) and membranebound (approximately 35 kDa) forms of b5R have identical catalytic domains and differ only in a hydrophobic domain at the N terminus of the membrane-bound form.…”
Section: Discussionmentioning
confidence: 99%
“…NADH cytochrome b 5 reductase is an FAD-containing protein with soluble and membrane-bound forms, each the product of the same gene through alternative promoters and alternative splicing (Tomatsu et al, 1989;Leroux et al, 2001). Both soluble (approximately 32 kDa) and membranebound (approximately 35 kDa) forms of b5R have identical catalytic domains and differ only in a hydrophobic domain at the N terminus of the membrane-bound form.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was isolated from whole blood with a commercial kit a. It is thought that the membrane‐bound form and soluble form of the enzyme are generated from alternative transcripts differing in the first exon, 1M and 1S, respectively . The canine CYB5R3 gene is located on chromosome 10, and exon 1M is found in the 530 bp gap (chr10: 22820169‐22820698) in the current version of the dog genome (CanFam3.1, NC_006592.3) .…”
Section: Methodsmentioning
confidence: 99%
“…There are 2 forms of b5R: a membrane‐bound form (the somatic form) and a soluble form (the erythrocytic form), which lacks the membrane anchor domain . Both types of b5R are encoded by the cytochrome b5 reductase ( CYB5R3 ) gene, and in rats and humans, it has reported that they are generated from alternative transcripts differing in the first exon . Two forms are composed of a flavin adenine dinucleotide (FAD) domain and an NADH‐binding domain .…”
mentioning
confidence: 99%
“…The membrane-bound isoform is anchored to the mitochondrial outer membrane, endoplasmic reticulum and plasma membrane of somatic cells and is involved in several metabolic processes including fatty acid desaturation and elongation, cholesterol biosynthesis and cytochrome P450-dependent drug metabolism [ 2 ]. Studies on transcriptional and translational mechanisms of CYB5R3 have clarified that the organization of the 5′ gene region is not conserved between humans and rodents and that insertion of Alu elements into the first exon of the human gene may have contributed to its dynamic evolution [ 3 ]. There are two types of NADH-CYB5R3 deficiency, depending on which isoform is involved.…”
Section: Introductionmentioning
confidence: 99%